THE IMPORTANCE OF THE "RAPPORT" TECHNIQUE IN CONCILIATION HEARINGS HELD AT THE CEJUSC OF THE SENADOR CANEDO EVANGELICAL COLLEGE (CIPEEX, 2022)
FESCAN'S CEJUSC IS A NEUTRAL ENVIRONMENT THAT OFFERS THE COMMUNITY FREE ACCESS TOJUSTICE. ON THE OTHER HAND, IT PROVIDES THE STUDENTS WITH A STRUCTURE, EQUIVALENT TO A JUDICIALUNIT, THAT IS, THE OPPORTUNITY TO SOLVE A CONFLICT IN A CONSENSUAL MANNER, WITHOUT ALL THE JUDICIALAPPARATUS INVOLVED. THE "RAPPORT" TECHNIQUE, OR "ACTIVE LISTENING", IS PART OF THE PSYCHOLOGYAREA, USED TO CREATE A CONNECTION, A COMMUNICATION BETWEEN THE PARTIES. THUS, THEMEDIATOR/CONCILIATOR/ADVOCATE STRATEGICALLY USES THE "RAPPORT" TECHNIQUE TO BUILD CREDIBILITYBETWEEN THE PARTIES TO RESOLVE THE CONFLICT. THIS PAPER AIMS TO ANALYZE THE CONTRIBUTIONS OF THE"RAPPORT" TECHNIQUE DURING THE HEARINGS HELD AT THE CONFLICT RESOLUTION JUDICIARY CENTER(CEJUSC) OF THE EVANGELICAL COLLEGE OF SENADOR CANEDO. WE INTEND TO UNDERSTAND THEIMPORTANCE OF THE CEJUSC THROUGH A QUANTITATIVE RESEARCH, THAT IS, WE WILL ANALYZE IF THE USEOF THE "RAPPORT" TECHNIQUE IN THE HEARINGS AND SELF-COMPOSITIVE SESSIONS COLLABORATED IN THERESOLUTION OF THE PROBLEMS PRESENTED BY THE COMMUNITY. HOWEVER, TO OBTAIN THE BEST SOLUTION TOTHE PROBLEM PRESENTED, IT IS NECESSARY TO APPLY TECHNIQUES TO BRING THE PARTIES TOGETHER. FINALLY,THIS PAPER AIMS TO DEMONSTRATE THAT THE "RAPPORT" TECHNIQUE IS NECESSARY FOR THE CEJUSC, WHICHIS AN IMPORTANT INSTANCE TO SOLVE A CONFLICT THAT CAN BE MEDIATED OR CONCILIATED, EVEN BEFORE ITIS TAKEN TO THE JUDICIARY.
Keywords: rapport; cejusc; extrajudicial means